Involvement of glutathione in the cytotoxicity of 9-isothiocyanatoacridine - Paulíková, Helena; Bajdichová, Mária; Šovčíková, Andrea; Sabolová, Danica (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2005)
Isothiocyanates (ITCs) are phytochemicals with promising cancer-preventive potential. To elucidate the mechanism of cytotoxicity of ITCs, their accumulation by cells and the role of intracellular glutathione, fluorescent 9-isothiocyanatoacridine (AcITC) was synthesized. The kinetic parameters for the reactions of AcITC with thiols were estimated and the influence of AcITC on human chronic myeloid leukemia cell line (K562) in regard to intracellular glutathione was studied. Cytotoxicity was evaluated by MTT assay, IC(50)=29.2 +/- 2.5 microM (48 h incubation). This acridine derivative was able to induce apoptosis of cells (morphological changes of cells and DNA fragmentation were observed) at least within certain dose that only decreased the level of intracellular glutathione, excessive doses (completely depleted intracellular pool of glutathione) induced necrosis rather than apoptosis. Our results indicated that apoptosis of leukemia cells induced by ITC is possible only if intracellular glutathione is not entirely depleted.
Keywords: Acridines; Leukemia L1210; apoptóza; K562 Cells; akridiny; Glutathione; leukemie L1210; fragmentace DNA; DNA Fragmentation; Mice; Tumor Cells, Cultured; buňky K562; zvířata; Humans; glutathion; viabilita buněk; Cell Survival; myši; nádorové buňky kultivované; lidé; Apoptosis; Animals